Pengembangan Penuntun Praktikum Kimia Dasar I Terintegrasi Pendekatan Inkuiri - Laila Tussifah Lubis; Ramlan Silaban; Iis Siti Jahro (Pascasarjana Universitas Negeri Medan, 2016)
Abstract-This research aimed to obtain Basic Chemistry I Practical Guidance Integrated Approach Inquiry that is easily understood and fit for use in Universitas Muhammaditah Tapanuli Selatan (UMTS) Padangsidimpuan. The method used is research and development (research and development) that is limited to the development, validation and testing of the product. Guidance lab developed based syntax inquiry approach. The instruments used were a questionnaire validation, observation sheets affective and psychomotor assessment. As a sample is student of chemical education at UMTS taken by purposive sampling. Guidance has been prepared validated by lecturers that have a minimum educational S2. Lecturer validation results against from 24 aspects assessed gained an average of 3.88, which means that the basic chemistry lab guide I used an integrated approach worthy of inquiry. Results limited trial gained an average of 69.31 pretest and post-test average of 82.73 and a score gain of 0.43 which means that the basic chemistry lab guide I can improve student learning outcomes. Results of the assessment of affective students gained an average of 2.5 and the assessment of psychomotor students gained an average of 2.34, which means that the value of affective and psychomotor student are good. The results of this study indicate that the basic chemistry lab guides I in UMTS is not accordance with the syllabus. Retrieved the guiding basic chemistry I that integrated guidance lab inquiry in accordance with the syllabus and fit for use. Guidance basic chemistry lab inquiry I integrated approach can improve student learning outcomes in the cognitive, affective and psychomotor. Keywords: Research and Development, Practical Guide, Basic Chemistry I, Inquiry Approach